Saprolegniosis in Nile Tilapia: Identification, Molecular Characterization, and Phylogenetic Analysis of Two Novel Pathogenic Saprolegnia Strains. Issue 1 (6th February 2017) - Zahran, Eman; Hafez, Elsayed E.; Mohd Altaf Hossain, Ferdaus; Elhadidy, Mohamed; Shaheen, Adel A.
Abstract: Saprolegniosis is a fungal infection that leads to huge economic losses in tilapia aquaculture. Saprolegnia spp. are usually implicated as the etiological agents, but their identification is sometimes troublesome and confusing. In this study, two Saprolegnia strains (ManS22 and ManS33) were isolated from Nile Tilapia Oreochromis niloticus suffering from saprolegniosis. Both isolates were characterized morphologically and from internal transcribed spacer (ITS) sequence data. Additionally, both strains were tested for pathogenicity, and they were highly pathogenic and caused cumulative mortalities of 88.9% and 95.6%, respectively. Initially, the two strains were identified, by morphology of sexual and asexual stages, as members of the genus Saprolegnia . For more definitive identification and characterization, the ITS region of the ribosomal RNA genes was amplified and sequenced, and sequences were compared with other known sequences in GenBank. A phylogenetic tree constructed using the neighbor‐joining method revealed that the two strains fell into two clusters within the species Saprolegnia parasitica . Cluster 1 included the ManS33 strain and cluster 2 the ManS22 strain. Cluster 1 grouped the ManS33 strain with other S. parasitica stains and shared 97–99% sequence similarity. Cluster 2 contained only the ManS22 strain and shared 93–94% similarity to several reference sequences of S. parasitica strains. Therefore, our findings suggest that ManS22 represents a newly described strain of S. parasitica . Received April 19, 2016; accepted October 27, 2016 Published online February 6, 2017